Experimental investigation of surface characterization of thin liquid layers on a solid substrate under different heating processes - Habeeb Mohamed Mohamed Khalifa (2009)
Heating a thin layer of silicone oil gives rise to convective cell pattern formation on the surface. These convective cells are commonly termed as Benard cells which are gaining interests in both academic research and in industrial applications. Presently, extensive research has been done in single-thin-liquid-layers (STLL) but not in two-immiscible-liquid-layer (TILL) systems. Therefore, the author investigates the feasibility of convective cell pattern formation on the silicone oil surface in both STLL (Phase 1 to 3) and TILL (Phase 4 to 6) systems. A simple shadowgraph technique comprising a mirror, a torch and a “filter” medium was used. The viscosity (centistokes, cSt) is varied as 50, 5 and 100 respectively in Phase 1, 2 and 3. In Phase 4 (50cSt) and 5 (5cSt), water was used as a base medium for silicone oil. In Phase 6, varying concentrations of Sodium Dodecyl Sulphate (SDS) surfactant was used as a base medium for Si oil and this was to study the effect of reducing surface tension in pattern formation.